Strategi FKUB dalam Penyelesaian Konflik Keagamaan dan upaya dalam Merawat Kerukunan Antar Umat Beragama di Kabupaten Keerom - Putra, Muhammad Irwan; Gani, Zulrijal Bushido; Endradi, Ardio Bayu (AL-MIKRAJ Jurnal Studi Islam dan Humaniora, 2024)
This research uses a qualitative approach with descriptive analysis. The data that researchers obtained was based on the results of observations and interviews with informants. The results of the research show that the factors causing social religious conflict in Keerom Regency are social jealousy between indigenous communities towards immigrants in Papua (economic disparities, welfare, employment opportunities, etc.), regional election events, black campaigns containing SARA, egocentrism & personal/group aggressiveness in religion and religion. Differences in cultural value orientations and individual and group interests. Meanwhile, FKUB's steps for resolving conflict in Keerom Regency, namely FKUB, are strengthening consolidation and communication between various parties, including FORKOPIMDA, religious leaders, community leaders and traditional leaders, opening space for dialogue, deliberation and mediation to accommodate aspirations from various elements of society. Arbitration (settlement of problems outside of court). Meanwhile, efforts to maintain inter-religious harmony carried out by FKUB include increasing the intensity of socialization, dialogue & deliberation activities involving various elements of society in the district. Keerom. Carrying out socialization of peaceful campaigns in General Elections, Regional Head Elections which are vulnerable to the use of SARA issues in politics. Carrying out conflict resolution training for religious leaders and members of the FKUB, religious moderation socialization program for the community in Keerom district, maintaining routine meetings between religious leaders, community leaders & traditional leaders and encouraging continuous support from the Keerom Regional Government in efforts to maintain harmony between religious communities